ANALISISIS EFEK DIKLAT DAN QUALITY OF WORK LIFE TERHADAP KINERJA PEGAWAI MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Masduki masduki; survival survival (JIM (Jurnal Ilmu Manajemen), 2023)
ABSTRACT  The purpose of this study was to prove the effect of training and quality of work life on employee performance through organizational citizenship behavior. The population in this study were all employees in Gadingrejo Subdistrict, Pasuruan City who were civil servants, namely 1 sub-district office totaling 18 employees, 8 village offices totaling 66 employees, so that in total there were 84 employees. The data analysis technique used smartPLS software version 4.0.The conclusion of the study is that training is able to improve employee performance. Training is not able to improve organizational citizenship behavior. Quality of work life is not able to improve employee performance. Quality of work life is able to improve employee organizational citizenship behavior. Organizational citizenship behavior is able to improve employee performance. Training is not able to improve employee performance mediated by organizational citizenship behavior. Quality of work life is able to improve employee performance mediated by organizational citizenship behavior. Keywords: Training, Quality of Work Life, Organizational Citizenship Behavior, Employee Performance.ABSTRAK  Tujuan penelitian ini adalah untuk membuktikan efek diklat dan quality of work life terhadap kinerja pegawai melalui organizational citizenship behavior. Penelitian ini menggunakan pendekatan penelitian kuantitatif. populasi dalam penelitian ini adalah seluruh pegawai di lingkungan Kecamatan Gadingrejo Kota Pasuruan yang berstatus PNS yaitu 84 pegawai. Teknik analisis data yang digunakan software smartPLS versi 4.0.Kesimpulan penelitian adalah Diklat mampu meningkatkan kinerja pegawai. Diklat tidak mampu meningkatkan organizational citizenship behavior. Quality of work life tidak mampu meningkatkan kinerja pegawai. Quality of work life mampu meningkatkan organizational citizenship behavior pegawai. Organizational citizenship behavior mampu meningkatkan kinerja pegawai. Diklat tidak mampu meningkatkan kinerja pegawai yang dimediasi organizational citizenship behavior. Quality of work life mampu meningkatkan kinerja pegawai yang dimediasi organizational citizenship behavior. Kata Kunci: Diklat, Quality of Work Life, Organizational Citizenship Behavior, Kinerja Pegawai.